2014
DOI: 10.1038/cmi.2014.46
|View full text |Cite
|
Sign up to set email alerts
|

Immune cells in term and preterm labor

Abstract: Labor resembles an inflammatory response that includes secretion of cytokines/chemokines by resident and infiltrating immune cells into reproductive tissues and the maternal/fetal interface. Untimely activation of these inflammatory pathways leads to preterm labor, which can result in preterm birth. Preterm birth is a major determinant of neonatal mortality and morbidity; therefore, the elucidation of the process of labor at a cellular and molecular level is essential for understanding the pathophysiology of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
330
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 392 publications
(364 citation statements)
references
References 145 publications
(230 reference statements)
18
330
0
7
Order By: Relevance
“…Although there is no doubt that the maternal circulating leukocytes are activated prior to and during the process of labor [26][27][28], the findings, herein, support the concept that the maternal-fetal interface (decidua basalis and choriodecidua or decidua parietalis) is an enriched microenvironment that includes specific leukocyte subsets during the process of labor [22,33]. We found that choriodecidual leukocytes overexpressed several genes associated with cell migration and regulation of immune response.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Although there is no doubt that the maternal circulating leukocytes are activated prior to and during the process of labor [26][27][28], the findings, herein, support the concept that the maternal-fetal interface (decidua basalis and choriodecidua or decidua parietalis) is an enriched microenvironment that includes specific leukocyte subsets during the process of labor [22,33]. We found that choriodecidual leukocytes overexpressed several genes associated with cell migration and regulation of immune response.…”
Section: Resultssupporting
confidence: 73%
“…Decidua parietalis is composed of stroma-type cells, glandular cells, and leukocytes [18][19][20][21], and the portion that is attainable is attached to the chorioamniotic membranes; therefore, this anatomical site is known as the choriodecidua [16]. Since the choriodecidua represents the major site of fetal antigenic exposure to the maternal immune system, our studies have focused on understanding the mechanisms whereby maternal leukocytes are recruited into the maternal-fetal interface and their role in the processes of term and preterm labor [22].…”
Section: Introductionmentioning
confidence: 99%
“…111,112 The endothelium system is critical player of innate defense via releasing inflammatory cytokines and chemokines in the first barrier to recruit monocytes, neutrophils, eosinophils and basophils from the circulation. [113][114][115][116] TLR stimulation induce phenotypic and functional maturation of DC into potent antigen-presenting cells which efficiently initiate and control adaptive immune responses, while in combination with IFN-γ could induce M1 macrophage polarization that is critical for phagocytosis and killing of invading pathogens.…”
Section: Cellular Regulation Of Innate Immunity and Inflammationmentioning
confidence: 99%
“…Notably, network analysis of the 212 mRNA targets of the 6 significantly upregulated miRNAs identified tumor necrosis factor (TNF) as a central node of a network that was enriched for DNA replication. TNF-induced inflammatory response is associated with preterm birth, 21,22 and levels of TNF are increased in the amniotic fluid from cases of preterm labor 22 . Several DNA methyltransferases were also identified within the network, which suggests that additional layers of epigenetic control are involved.…”
Section: Discussionmentioning
confidence: 99%